The Effect of Receptie Theory on Legal Concept of “Adat Barenti Lako Syara’, Syara Barenti Lako Kitabullah” - Dianto Dianto (Journal of Transcendental Law, 2020)
Receptie theory of Snouck Hurgonje's thought requires that Islam be valid if it has been perceived by customary law. The perception of a starting point between Islamic law and customary law was mediated by Syahrial Abbas with his split bamboo theory. However, the concept of "Adat Barenti Lako Syara’, Syara Barenti Lako Kitabullah" requires that customary law be valid or accepted if it has been validated by Islamic law. Employing a normative method and a philosophical approach, this paper examined the effect of the receptie theory on the legal concept of "Barenti Lako Syara', Syara Barenti Lako Kitabullah". This paper concluded that the receptie theory could not influence the legal concept of "Adat Barenti Lako Syara’, Syara Barenti Lako Kitabullah" because customary law can be applied if it has been verified by Islamic law.